"Can touch this": Cross‐modal shape categorization performance is associated with microstructural characteristics of white matter association pathways. Issue 2 (3rd October 2016) - Lee Masson, Haemy; Wallraven, Christian; Petit, Laurent
Abstract: Previous studies on visuo‐haptic shape processing provide evidence that visually learned shape information can transfer to the haptic domain. In particular, recent neuroimaging studies have shown that visually learned novel objects that were haptically tested recruited parts of the ventral pathway from early visual cortex to the temporal lobe. Interestingly, in such tasks considerable individual variation in cross‐modal transfer performance was observed. Here, we investigate whether this individual variation may be reflected in microstructural characteristics of white‐matter (WM) pathways. We first trained participants on a fine‐grained categorization task of novel shapes in the visual domain, followed by a haptic categorization test. We then correlated visual training‐performance and haptic test‐performance, as well as performance on a symbol‐coding task requiring visuo‐motor dexterity with microstructural properties of WM bundles potentially involved in visuo‐haptic processing (the inferior longitudinal fasciculus [ILF], the fronto‐temporal part of the superior longitudinal fasciculus [SLFft ] and the vertical occipital fasciculus [VOF]). Behavioral results showed that haptic categorization performance was good on average but exhibited large inter‐individual variability. Haptic performance also was correlated with performance in the symbol‐coding task. WM analyses showed that fast visual learners exhibited higher fractional anisotropy (FA) in left SLFft and left VOF. Importantly, haptic test‐performance (and symbol‐coding performance) correlated with FA in ILF and with axial diffusivity in SLFft . These findings provide clear evidence that individual variation in visuo‐haptic performance can be linked to microstructural characteristics of WM pathways. Hum Brain Mapp 38:842–854, 2017 . ©2016 Wiley Periodicals, Inc.